Penggunaan Media Sosial untuk Penyebarluasan Informasi Peringatan Dini Banjir ke Masyarakat (Studi Kasus: BPBD Provinsi DKI Jakarta) - Hadi Syafruddin Harahap (Jurnal Syntax Admiration, 2024)
This study aims to analyze the role of social media in the dissemination of flood early warning information carried out by the Jakarta Provincial BPBD. Against the background of the importance of an effective early warning system, this study explores the use of social media as a communication channel that can reach the wider community quickly. Using a qualitative approach, this case study observed post data from BPBD social media platforms such as X (Twitter), Facebook, and Instagram in the period from November 2023 to February 2024. The results of the study show that BPBD actively uses social media to provide early warning information related to floods from various sources, such as upstream rain, local rain, and coastal floods. The conclusion of this study is that social media is effective in increasing public preparedness against potential floods, despite the challenges in maintaining public trust and ensuring understanding of the message conveyed.